Magnetic conductivity gradient controllable laminated power inductor internal structure preparation process and product thereof

By adopting a stacked structure with controllable magnetic permeability gradient in the inductor, and using the combination of FeSiCr and NiZnCuFeO3 materials, the high magnetic loss problem of the inductor in the low load state is solved, achieving more efficient energy conversion and stable performance.

CN119560298AActive Publication Date: 2025-03-04DONGGUAN SANTI MICROELECTRONICS TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411645538.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-04
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing inductors have a large magnetic loss in low load or sleep states, which affects efficiency and performance.

Method used

The internal structure preparation process of the magnetic permeability gradient controllable stacked power inductor is adopted. Through the lamination process, the combination of FeSiCr semi-cured sheet and NiZnCuFeO3 slurry layer is used to adjust the magnetic force line distribution to achieve gradient controllability.

Benefits of technology

Reduce magnetic loss in low load or sleep states, improve the efficiency and performance of the inductor, and maintain efficient power conversion under high load states.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005139612680000061
    Figure BDA0005139612680000061
  • Figure BDA0005139612680000071
    Figure BDA0005139612680000071
  • Figure BDA0005139612680000101
    Figure BDA0005139612680000101
Patent Text Reader

Abstract

The invention relates to the technical field of inductors, in particular to a magnetic conductivity gradient controllable laminated power inductor internal structure preparation process and a product thereof, the magnetic conductivity gradient controllable laminated power inductor internal structure preparation process comprises the following preparation steps: S1, a lamination process is adopted to prepare a plurality of FeSiCr prepregs by using FeSiCr slurry, the prepregs used for the first layer and the top layer are not punched, and the rest prepregs are punched; s2, NiZnCuFeO3 slurry is printed on the FeSiCr prepreg, a NiZnCuFeO3 circuit layer is formed, and the circuit layer needs to pass through the holes; s3, an inner electrode wire is printed on the surface of the NiZnCuFeO3 circuit layer, the edge of an inner electrode ring cannot exceed the edge of the NiZnCuFeO3 circuit layer, the inner electrode ring of the first-layer board prepreg does not need to penetrate through the hole, and the inner electrode wires of the other prepregs need to penetrate through the hole; and S4, after the inner electrode wire is printed on the first layer of prepreg, placing the second layer of prepreg, repeating the steps S2-S3, placing the third prepreg, repeating the steps S2-S3, and so on, and finally placing the top layer of prepreg to form a multi-layer structure and obtain the internal structure of the inductor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of inductor technology, and more specifically, to a process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient and a product thereof. Background Art

[0002] The application of inductors in chips is mainly as a key component of the power supply module, which plays the role of powering the front end of GPU, CPU, ASIC, FPGA and other chips. Inductors store and release energy through the principle of electromagnetic induction, thereby playing the role of smoothing current, reducing noise, stabilizing power supply, etc. in the circuit. When the chip is in low load or sleep state, the actual current passing through the inductor is small. At this time, the loss of the inductor is mainly reflected in the magnetic loss, that is, in the low current state, the loss of the inductor is mainly caused by the magnetic loss of the magnetic core, mainly including hysteresis loss, eddy current loss, etc. These losses will affect the efficiency and performance of the inductor. Summary of the invention

[0003] In order to reduce the magnetic loss of the inductor when the chip is in a low-load or dormant state, the present application provides a process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient and its product.

[0004] In a first aspect, the present application provides a process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient, using the following technical solution: A process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient, comprising the following preparation steps: S1. Using a lamination process and FeSiCr slurry to prepare a plurality of FeSiCr prepregs, wherein the prepregs used for the first layer and the top layer are not perforated, and the remaining prepregs are perforated; S2, printing NiZnCuFeO3 slurry on the FeSiCr prepreg to form a NiZnCuFeO3 circuit layer, and the circuit layer must pass through the holes; wherein, the first layer of the prepreg does not need to pass through the holes, and the top layer of the prepreg does not need to be printed with NiZnCuFeO3 slurry; S3. Print the inner electrode line on the surface of the NiZnCuFeO3 circuit layer, and the edge of the inner electrode circle cannot exceed the edge of the NiZnCuFeO3 circuit layer. The inner electrode circle of the first layer of prepreg does not need to pass through the hole, and the inner electrode lines of the other prepregs need to pass through the hole; S4. After the first layer of semi-cured sheet is printed with the inner electrode line, the second layer of semi-cured sheet is placed, and steps S2-S3 are repeated. Then the third layer of semi-cured sheet is placed, and steps S2-S3 are repeated, and so on, until the required number of layers is reached. Finally, the top layer of semi-cured sheet is placed to form a multi-layer structure to obtain the internal structure of the inductor.

[0005] By adopting the above technical solution, the system coordination of the FeSiCr prepreg and the NiZnCuFeO3 layer is adjusted to achieve gradient control. When the chip is under low load / sleep, the magnetic lines of force inside the inductor are mainly concentrated in the NiZnCuFeO3 layer. At this time, the inductor exhibits high inductance. As the load of the chip increases, the NiZnCuFeO3 layer gradually becomes magnetically saturated, and the corresponding magnetic lines of force are concentrated in the FeSiCr layer. At this time, the inductor exhibits low inductance, achieving an overall higher power conversion efficiency in the full power range of DC-DC conversion and reducing losses.

[0006] At the same time, in the present application, by printing NiZnCuFeO3 slurry on the FeSiCr semi-cured sheet and printing the inner electrode line, a multi-layer structure inductor is formed, which can enhance the electromagnetic induction effect and improve the energy storage and release efficiency, thereby playing a better role in smoothing current, reducing noise and stabilizing power supply in the circuit.

[0007] Preferably, the thickness of the FeSiCr prepreg and the NiZnCuFeO3 layer is 1:(0.2-0.5).

[0008] By adopting the above technical solution, the thickness of the FeSiCr prepreg and the NiZnCuFeO3 layer is convenient to realize and reduce the loss of the inductor. The structural stability and reliability of the inductor are ensured, and it can withstand long-term operation of high power and high frequency, reduce the failure rate of the inductor during use, and extend the service life of the inductor.

[0009] Preferably, the FeSiCr slurry is prepared by the following method: 1) ball milling the FeSiCr powder to 200-300 nm to obtain a first mixed metal powder; 2) Grinding the first mixed metal powder, the first solvent, the adhesive, the coupling agent, the plasticizer and polymethyl methacrylate to a viscosity of 1200-2000 cps to obtain FeSiCr slurry, wherein the adhesive is composed of ethyl cellulose, polyvinyl butyral resin and polyvinyl alcohol.

[0010] Preferably, the weight parts of the raw materials used to prepare the FeSiCr slurry are as follows: FeSiCr powder 110-140 parts 100-150 parts of the first solvent Adhesive 10-20 parts 3-5 parts of coupling agent Plasticizer 0.8-1 part 40-50 parts of polymethyl methacrylate.

[0011] By adopting the above technical solution, the FeSiCr prepreg prepared by the FeSiCr slurry can reduce the magnetic loss of the inductor under low load or dormant state, reduce eddy current loss and hysteresis loss, thereby improving the efficiency and performance of the inductor.

[0012] After mixing iron powder, silicon powder and chromium powder and then ball milling, it helps to better disperse the metal powder in the solvent and adhesive, improve the uniformity and stability of the slurry, and make the internal structure of the subsequently prepared inductor more dense and uniform. At the same time, due to the small particle size and uniform distribution of the metal powder in the slurry, as well as the good adhesion of the adhesive, the internal structure of the prepared inductor has lower loss. Especially under low load or dormant conditions, the loss of the inductor is mainly caused by the magnetic loss of the magnetic core, and the inductor prepared by this slurry can effectively reduce hysteresis loss and eddy current loss, and improve the efficiency of the inductor.

[0013] The first mixed metal powder is ground with the first solvent, adhesive, coupling agent, plasticizer and polymethyl methacrylate until the viscosity reaches 1200-2000cps, so that the FeSiCr slurry has good printability and formability, can be easily coated on the substrate through the printing process, and form a stable inductor internal structure through the subsequent curing process. At the same time, it is conducive to the subsequent printing and coating of NiZnCuFeO3 slurry.

[0014] In the present application, the binder is prepared by ethyl cellulose, polyvinyl butyral resin and polyvinyl alcohol, so that the good compatibility between the components of the FeSiCr slurry and the strong bonding effect of the binder make it less likely for the inductor to experience performance degradation or failure during long-term use.

[0015] Preferably, the weight ratio of the ethyl cellulose, the polymethyl methacrylate and the polyvinyl alcohol is 5:(1-3):(4-6).

[0016] By adopting the above technical solution, the dosage of ethyl cellulose, polyvinyl butyral resin and polyvinyl alcohol is optimized, which helps to accurately control the viscosity of the slurry. As the main adhesive component, ethyl cellulose provides a stable skeleton for the slurry with its high viscosity characteristics. The addition of polymethyl methacrylate and polyvinyl alcohol can adjust the viscosity of the slurry, making it more suitable for coating and printing processes. At the same time, polyvinyl alcohol has good solubility, which can help metal powder and other ingredients to be better dispersed in the solvent to form a uniform slurry. This helps to evenly distribute the metal powder in the subsequent preparation process of the internal structure of the inductor, thereby improving the performance of the inductor.

[0017] Preferably, the NiZnCuFeO3 slurry is prepared by the following method: A. Mix nickel oxide powder, zinc oxide powder, copper oxide powder and ferric oxide powder, ball mill them to 200-500 nm, and sinter them to obtain a second mixed metal powder; B. Mix polymethyl methacrylate, a second solvent, epoxy resin, ethyl cellulose and a curing agent, add a second mixed metal powder and a dispersant, grind and stir, and obtain a NiZnCuFeO3 slurry grinded to a viscosity of 2000-4000cps.

[0018] Preferably, the weight parts of the raw materials used to prepare the NiZnCuFeO3 slurry are as follows: Nickel oxide powder 25-30 parts 20-30 parts of zinc oxide powder 15-20 parts of copper oxide powder 20-30 parts of iron oxide powder Polymethyl methacrylate 5-10 parts Second solvent 100-150 parts Epoxy resin 10-15 parts 6-10 parts of ethyl cellulose 1-3 parts of curing agent Dispersant 3-5 parts.

[0019] Preferably, the firing process is as follows: heating from room temperature to 200-300°C over 1-2 hours, then heating to 500-600°C over 2-3 hours, keeping warm for 1-2 hours, then heating to 800-900°C over 1-2 hours, then heating to 1100-1200°C over 1-2 hours, and keeping warm for 2.5-4 hours.

[0020] By adopting the above technical solution, the prepared NiZnCuFeO3 slurry has a low magnetic loss characteristic. The slurry prepared by the NiZnCuFeO3 is printed in the internal structure of the inductor and used in combination with the FeSiCr prepreg to achieve the required magnetic permeability gradient and chemical stability, which can further reduce the magnetic loss of the inductor in a low-load or dormant state.

[0021] By mixing nickel oxide powder, zinc oxide powder, copper oxide powder and iron oxide powder and then ball milling, the powder can be ground to 200-500nm, which helps to obtain better dispersion and uniformity in the subsequent preparation of slurry, thereby improving the overall performance of the slurry. By adding ingredients such as polymethyl methacrylate, a second solvent, epoxy resin, ethyl cellulose and a curing agent, and grinding and stirring, a NiZnCuFeO3 slurry with a viscosity of 2000-4000cps is obtained, so that the NiZnCuFeO3 slurry has good fluidity and is easy to print and coat during the preparation of the inductor. The addition of a dispersant during the preparation process helps to evenly disperse the second mixed metal powder in the slurry so that the metal powder can be evenly distributed in the internal structure of the inductor, thereby improving the electromagnetic performance and stability of the inductor.

[0022] Preferably, the epoxy resin has a viscosity of 2000-10000 mPa.s (25° C.) and an epoxy value of 3-20 eq / 100 g.

[0023] By adopting the above technical solution, using moderate viscosity and epoxy value makes the epoxy resin easier to control and operate during the preparation and curing process, and can be better mixed with metal powder and other components during the curing process to form a dense structure, which helps to improve the mechanical strength and reliability of the inductor.

[0024] Preferably, the relative magnetic permeability of the FeSiCr prepreg is 20-60, and the saturation magnetic flux of the FeSiCr prepreg is 0.8-1.5T.

[0025] Preferably, the relative magnetic permeability of the NiZnCuFeO3 slurry layer is 40-200, and the saturation magnetic flux of the NiZnCuFeO3 slurry layer is 0.01-0.5T.

[0026] By adopting the above technical solution, the relative magnetic permeability and saturation magnetic flux density of the FeSiCr prepreg and the NiZnCuFeO3 slurry layer are optimized, so that the inductor has lower magnetic loss at high frequency while maintaining high efficiency at high current, thereby improving the energy efficiency ratio of the inductor.

[0027] In a second aspect, the present application provides an inductor internal structure obtained by a process for preparing an internal structure of a laminated power inductor with controllable magnetic permeability gradient, and adopts the following technical solution: The invention discloses an inductor internal structure obtained by a preparation process of an internal structure of a laminated power inductor with controllable magnetic permeability gradient, comprising a FeSiCr prepreg, a NiZnCuFeO3 slurry layer and an inner electrode wire, wherein the NiZnCuFeO3 slurry layer is formed on the upper surface of the FeSiCr prepreg by printing, the structural size and thickness of the NiZnCuFeO3 slurry layer are adjustable to achieve controllable inductance gradient, the inner electrode wire is formed on the upper surface of the NiZnCuFeO3 slurry layer by printing, and the FeSiCr prepreg, the NiZnCuFeO3 slurry layer and the inner electrode wire are stacked several times in sequence.

[0028] By adopting the above technical solution, a multi-layer structure is formed. This structural design not only improves the structural stability and reliability of the inductor, but also can withstand long-term operation of high power and high frequency, reduces the failure rate of the inductor during use, and extends the service life of the inductor.

[0029] In summary, this application has the following beneficial effects: 1. Gradient control is achieved by adjusting the system coordination of the FeSiCr prepreg and the NiZnCuFeO3 layer. When the chip is under low load / sleep, the magnetic lines of force inside the inductor are mainly concentrated in the NiZnCuFeO3 layer. At this time, the inductor presents a high inductance. As the load of the chip increases, the NiZnCuFeO3 layer gradually becomes magnetically saturated, and the corresponding magnetic lines of force are concentrated in the FeSiCr layer. At this time, the inductor presents a low inductance, achieving an overall higher power conversion efficiency in the full power range of DC-DC conversion. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic diagram of a single stacking forming process of a controllable permeability gradient laminated power inductor in this application.

[0031] Explanation of the reference numerals: 1. FeSiCr prepreg; 2. NiZnCuFeO3 slurry layer; 3. Inner electrode line.

[0032] Preparation Example Polymethyl methacrylate was purchased from Dongguan Hongkuo Plastic Co., Ltd., model number 8137, and its origin was Dow, Thailand.

[0033] Titanate coupling agent was purchased from Shandong Hui'an Chemical Co., Ltd. with a CAS number of 61417-49-0.

[0034] The aluminate coupling agent was purchased from Shandong Guohua Chemical Co., Ltd. and the implementation standard was the national standard.

[0035] Polyvinyl butyral resin was purchased from Hubei Yamade Biopharmaceutical Co., Ltd., model number is Butvar-76.

[0036] FeSiCr powder was purchased from Qinghe County Tebo Metal Materials Co., Ltd. with model number 7485210.

[0037] Preparation Example 1 A FeSiCr slurry is prepared by the following method: 1. Ball mill 110 g of FeSiCr powder to 200-240 nm to obtain a first mixed metal powder; 2) Grind the first mixed metal powder, 100 g of the first solvent (ethyl acetate), 10 g of the adhesive, 3 g of the coupling agent (KH550), 0.8 g of the plasticizer (diisononyl phthalate) and 40 g of polymethyl methacrylate to a viscosity of 1200 cps to obtain a FeSiCr slurry, wherein the binder is composed of ethyl cellulose, polyvinyl butyral resin and polyvinyl alcohol in a weight ratio of 5:1:4.

[0038] The molecular weight of polyvinyl alcohol is 2000.

[0039] The difference between Preparation Example 2-3 and Preparation Example 1 is that the types, amounts and experimental parameters of raw materials used to prepare FeSiCr slurry are different. The specific differences are shown in Table 1: Table 1 Preparation Examples 1-3, raw material types, amounts and experimental parameters for preparing FeSiCr slurries Preparation Example 4 A NiZnCuFeO3 slurry is prepared by the following method: 1. Mix 25 g of nickel oxide powder, 20 g of zinc oxide powder, 15 g of copper oxide powder and 20 g of ferric oxide powder, ball mill and grind to 200-300 nm, and sinter to obtain a second mixed metal powder; The firing process is as follows: raise the temperature from room temperature to 200°C over 1 hour, then raise the temperature to 500°C over 2 hours, keep warm for 1 hour, then raise the temperature to 800°C over 1 hour, then raise the temperature to 1100°C over 1 hour, and keep warm for 2.5 hours.

[0040] B. Mix 5 g of polymethyl methacrylate, 100 g of the second solvent (ethyl acetate), 10 g of epoxy resin, 6 g of ethyl cellulose and 1 g of curing agent (ethylenediamine), then add the second mixed metal powder and 3 g of dispersant (talcum powder), grind and stir to obtain NiZnCuFeO3 slurry ground to a viscosity of 2000 cps.

[0041] The epoxy resins used in the preparation examples are all bisphenol A epoxy resins. The viscosity of the epoxy resin in Preparation Example 1 is 200 mPa.s (25° C.) and the epoxy value is 3 eq / 100 g.

[0042] The difference between Preparation Example 5-6 and Preparation Example 4 is that the raw material types, amounts and experimental parameters for preparing NiZnCuFeO3 slurry are different. The specific differences are shown in Table 2: Table 2 Raw material types, amounts and experimental parameters for preparing NiZnCuFeO3 slurry in Preparation Examples 4-6 The firing process in Preparation Example 5 is as follows: raise the temperature from room temperature to 250°C over 1.5 hours, then raise the temperature to 550°C over 2.5 hours, keep warm for 1.5 hours, then raise the temperature to 850°C over 1.5 hours, then raise the temperature to 1150°C over 1.5 hours, and keep warm for 3.4 hours.

[0043] The firing process in Preparation Example 6 is as follows: raise the temperature from room temperature to 300°C over 2 hours, then raise the temperature to 600°C over 3 hours, keep warm for 2 hours, then raise the temperature to 900°C over 2 hours, then raise the temperature to 1200°C over 2 hours, and keep warm for 4 hours.

[0044] Preparation Comparative Example Preparation Comparative Example 1 A FeSiCr slurry. The difference between this comparative preparation example and preparation example 1 is that the binder is ethyl cellulose.

[0045] Preparation Comparative Example 2 A FeSiCr slurry. The difference between this comparative preparation example and preparation example 1 is that the binder is composed of polyvinyl butyral resin and polyvinyl alcohol in a weight ratio of 1:4.

[0046] Preparation Comparative Example 3 A FeSiCr slurry. The difference between this comparative preparation example and preparation example 1 is that polyvinyl alcohol is used instead of polymethyl methacrylate.

[0047] The molecular weight of polyvinyl alcohol is 2,000.

[0048] Preparation Comparative Example 4 A MoZnCuFeO3 slurry. The difference between this comparative preparation example and preparation example 1 is that molybdenum powder is used instead of nickel oxide powder.

[0049] Preparation Comparative Example 5 A NiFeCuFeO3 slurry. The difference between this comparative preparation example and preparation example 1 is that iron powder is used instead of zinc oxide powder.

[0050] Preparation Comparative Example 6 A NiZnCuFeO3 slurry. The difference between this comparative preparation example and preparation example 1 is that iron powder is used instead of copper oxide powder.

[0051] Preparation Comparative Example 7 A NiZnCuFeO3 slurry. The difference between this comparative preparation example and preparation example 1 is that polyvinyl alcohol is used instead of polymethyl methacrylate.

[0052] The molecular weight of polyvinyl alcohol is 2,000. Example

[0053] Example 1 An internal structure of a multilayer power inductor with controllable magnetic permeability gradient, such as Figure 1 As shown, the controllable permeability gradient laminated power inductor includes a FeSiCr prepreg 1, a NiZnCuFeO3 slurry layer 2 and an inner electrode wire 3, the NiZnCuFeO3 slurry layer 2 is formed on the upper surface of the FeSiCr prepreg 1 by printing, the inner electrode wire 3 is formed on the upper surface of the NiZnCuFeO3 slurry layer 2 by printing, and the FeSiCr prepreg 1, the NiZnCuFeO3 slurry layer 2 and the inner electrode wire 3 are stacked several times in sequence.

[0054] The internal structure of the controllable magnetic permeability gradient laminated power inductor is prepared by the following method: S1. Using a lamination process and FeSiCr slurry (Preparation Example 1) to prepare a number of FeSiCr prepregs, wherein the prepregs used for the first layer and the top layer are not perforated, and the remaining prepregs are perforated; S2, printing NiZnCuFeO3 slurry (preparation example 4) on the FeSiCr prepreg to form a NiZnCuFeO3 circuit layer, and the circuit layer must pass through the holes; wherein the first layer of the prepreg does not need to pass through the holes, and the top layer of the prepreg does not need to be printed with NiZnCuFeO3 slurry; S3, printing the inner electrode line (silver paste) on the surface of the NiZnCuFeO3 circuit layer, and the edge of the inner electrode circle cannot exceed the edge of the NiZnCuFeO3 circuit layer, wherein the inner electrode circle of the first layer of prepreg does not need to pass through the hole, and the inner electrode lines of the remaining prepregs need to pass through the hole; S4. After the first layer of semi-cured sheet is printed with the inner electrode line, the second layer of semi-cured sheet is placed, and steps S2-S3 are repeated. Then the third layer of semi-cured sheet is placed, and steps S2-S3 are repeated, and so on, until the required number of layers is reached. Finally, the top layer of semi-cured sheet is placed to form a multi-layer structure to obtain the internal structure of the inductor.

[0055] The relative magnetic permeability of the FeSiCr prepreg is 20, and the saturation magnetic flux of the FeSiCr prepreg is 0.8T.

[0056] The relative magnetic permeability of the NiZnCuFeO3 slurry layer is 40, and the saturation magnetic flux of the NiZnCuFeO3 slurry layer is 0.01T.

[0057] Example 2 An internal structure of a controllable magnetic permeability gradient laminated power inductor. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation example 2, and the NiZnCuFeO3 slurry comes from preparation example 5.

[0058] The relative magnetic permeability of the FeSiCr prepreg is 40, and the saturation magnetic flux of the FeSiCr prepreg is 1.2T.

[0059] The relative magnetic permeability of the NiZnCuFeO3 slurry layer is 100, and the saturation magnetic flux of the NiZnCuFeO3 slurry layer is 0.3T.

[0060] Example 3 An internal structure of a controllable permeability gradient laminated power inductor. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation example 3, and the NiZnCuFeO3 slurry comes from preparation example 6.

[0061] The relative magnetic permeability of the FeSiCr prepreg is 60, and the saturation magnetic flux of the FeSiCr prepreg is 1.5T.

[0062] The relative magnetic permeability of the NiZnCuFeO3 slurry layer is 200, and the saturation magnetic flux of the NiZnCuFeO3 slurry layer is 0.5T.

[0063] Example 4 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from the preparation of comparative example 1.

[0064] Example 5 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation comparative example 2.

[0065] Example 6 An internal structure of a laminated power inductor with controllable magnetic permeability gradient, the difference between this embodiment and embodiment 1 is that: The FeSiCr slurry is from Preparation Comparative Example 3.

[0066] Example 7 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation comparative example 4.

[0067] Example 8 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation comparative example 5.

[0068] Example 9 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation comparative example 6.

[0069] Example 10 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this embodiment and embodiment 1 is that the FeSiCr slurry comes from preparation comparative example 7.

[0070] Comparative Example Comparative Example 1 An internal structure of a laminated power inductor with controllable magnetic permeability gradient. The difference between this comparative example and Example 1 is that step S2 is omitted, and the inner electrode line (silver paste) is directly printed on the FeSiCr prepreg.

[0071] Detection method / test method Magnetic loss: Use BH tester SY-8212 to test magnetic loss. The larger the magnetic loss value, the more energy is converted into heat or other forms of energy and lost during the magnetization process, which will lead to reduced efficiency of the circuit or equipment.

[0072] Magnetic permeability test: Agilent 4991B equipment is used to test the magnetic permeability at 1kHz, and the fixture is 16454A. The higher the magnetic permeability, the easier it is for the material to be magnetized. Under the same magnetic field strength, materials with high magnetic permeability can produce stronger magnetic induction intensity.

[0073] Shedding test experiment: The internal structures of the inductors prepared in Examples 1-12 and Comparative Example 1 were placed in an environment with a temperature of 120°C, and were violently vibrated once every 1 hour. After being placed for 72 hours, the internal structures of the inductors were taken out and observed to see if they bulged or fell off. The experimental data are shown in Table 2: Table 2 Experimental data of Examples 1-12 and Comparative Example 1 By comparing Example 1 with Comparative Example 1, the magnetic loss value in Example 1 is lower than that in Comparative Example 1; the magnetic permeability in Comparative Example 1 is lower than that in Example 1; in the shedding test, delamination occurs in Comparative Example 1, indicating that the internal structure of the inductor prepared by the preparation process in the present application has lower magnetic loss, suitable magnetic flux and stable structural strength.

[0074] Comparing Example 1 with Example 4-5, the magnetic loss value of Example 4-5 is slightly higher than that of Example 1; the magnetic permeability in Example 4-5 is slightly lower than that of Example 1, and bubbles appear in Example 4 during the shedding experiment, while shedding occurs in Example 5. This indicates that in the present application, by preparing a binder using ethyl cellulose, polyvinyl butyral resin and polyvinyl alcohol, and then using the binder to prepare FeSiCr slurry, the magnetic flux and structural stability of the internal structure of the inductor can be improved, while the magnetic loss can also be reduced.

[0075] Comparing Example 1 with Example 6, the magnetic loss value of Example 6 is slightly higher than that of Example 1; the magnetic permeability in Example 6 is slightly lower than that in Example 1, and bubbles appear in Example 6 during the shedding experiment, indicating that in the present application, by using polymethyl methacrylate to prepare FeSiCr slurry, the magnetic flux and structural stability of the internal structure of the inductor can be improved, while the magnetic loss can also be reduced.

[0076] Comparing Example 1 with Examples 7-9, the magnetic loss value of Example 7-9 is higher than that of Example 1; the magnetic permeability in Example 7-9 is slightly lower than that of Example 1, indicating that the present application can increase the magnetic flux of the internal structure of the inductor while reducing the magnetic loss by preparing NiZnCuFeO3 slurry using a combination of nickel oxide powder, zinc oxide powder and copper oxide powder.

[0077] Comparing Example 1 with Example 10, the magnetic loss value of Example 10 is slightly higher than that of Example 1; the magnetic permeability in Example 10 is slightly lower than that in Example 1, and bubbles appear in Example 10 in the shedding experiment, indicating that in the present application, by preparing FeSiCr slurry with the participation of polymethyl methacrylate, the magnetic flux and structural stability of the internal structure of the inductor can be improved, and the magnetic loss can also be reduced.

[0078] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient, characterized in that: The method comprises the following preparation steps: S1. Using a lamination process and FeSiCr slurry to prepare a plurality of FeSiCr prepregs, wherein the prepregs used for the first layer and the top layer are not perforated, and the remaining prepregs are perforated; S2, printing NiZnCuFeO3 slurry on the FeSiCr prepreg to form a NiZnCuFeO3 circuit layer, and the circuit layer must pass through the holes; wherein, the first layer of the prepreg does not need to pass through the holes, and the top layer of the prepreg does not need to be printed with NiZnCuFeO3 slurry; S3. Print the inner electrode line on the surface of the NiZnCuFeO3 circuit layer, and the edge of the inner electrode circle cannot exceed the edge of the NiZnCuFeO3 circuit layer. The inner electrode circle of the first layer of prepreg does not need to pass through the hole, and the inner electrode lines of the other prepregs need to pass through the hole; S4. After the first layer of semi-cured sheet is printed with the inner electrode line, the second layer of semi-cured sheet is placed, and steps S2-S3 are repeated. Then the third layer of semi-cured sheet is placed, and steps S2-S3 are repeated, and so on, until the required number of layers is reached. Finally, the top layer of semi-cured sheet is placed to form a multi-layer structure to obtain the internal structure of the inductor.

2. The process for preparing the internal structure of a controllable magnetic permeability gradient laminated power inductor according to claim 1, characterized in that: The FeSiCr slurry is prepared by the following method: 1) ball milling the FeSiCr powder to 200-300 nm to obtain a first mixed metal powder; 2) Grinding the first mixed metal powder, the first solvent, the adhesive, the coupling agent, the plasticizer and polymethyl methacrylate to a viscosity of 1200-2000 cps to obtain FeSiCr slurry, wherein the adhesive is composed of ethyl cellulose, polyvinyl butyral resin and polyvinyl alcohol.

3. The process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient according to claim 2, characterized in that: The weight parts of the raw materials used to prepare the FeSiCr slurry are as follows: FeSiCr powder 110-140 parts 100-150 parts of the first solvent Adhesive 10-20 parts 3-5 parts of coupling agent Plasticizer 0.8-1 part 40-50 parts of polymethyl methacrylate.

4. The process for preparing the internal structure of a controllable magnetic permeability gradient laminated power inductor according to claim 1: the weight ratio of the ethyl cellulose, the polymethyl methacrylate and the polyvinyl alcohol is 5:(1-3):(4-6).

5. The process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient according to claim 4, characterized in that: The NiZnCuFeO3 slurry is prepared by the following method: A. Mix nickel oxide powder, zinc oxide powder, copper oxide powder and ferric oxide powder, ball mill them to 200-500 nm, and sinter them to obtain a second mixed metal powder; B. Mix polymethyl methacrylate, a second solvent, epoxy resin, ethyl cellulose and a curing agent, add a second mixed metal powder and a dispersant, grind and stir, and obtain a NiZnCuFeO3 slurry grinded to a viscosity of 2000-4000cps.

6. A process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient according to claim 5, characterized in that ,characterized in that, The weight parts of the raw materials used to prepare the NiZnCuFeO3 slurry are as follows: Nickel oxide powder 25-30 parts 20-30 parts of zinc oxide powder 15-20 parts of copper oxide powder 20-30 parts of iron oxide powder Polymethyl methacrylate 5-10 parts Second solvent 100-150 parts Epoxy resin 10-15 parts Ethyl cellulose 6-10 parts 1-3 parts of curing agent Dispersant 3-5 parts.

7. The process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient according to claim 1, characterized in that: The epoxy resin has a viscosity of 2000-10000 mPa.s (25° C.) and an epoxy value of 3-20 eq / 100 g.

8. The process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient according to claim 1, characterized in that: The relative magnetic permeability of the FeSiCr prepreg is 20-60, and the saturation magnetic flux of the FeSiCr prepreg is 0.8-1.5T.

9. The process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient according to claim 1, characterized in that: The relative magnetic permeability of the NiZnCuFeO3 slurry layer is 40-200, and the saturation magnetic flux of the NiZnCuFeO3 slurry layer is 0.01-0.5T.

10. An inductor internal structure according to any one of claims 1 to 9, wherein the process for preparing the internal structure of a laminated power inductor with controllable magnetic permeability gradient is characterized in that: The invention comprises a FeSiCr prepreg (1), a NiZnCuFeO3 slurry layer (2) and an inner electrode line (3), wherein the NiZnCuFeO3 slurry layer (2) is formed on the upper surface of the FeSiCr prepreg (1) by printing, the structural size and thickness of the NiZnCuFeO3 slurry layer (2) are adjustable to achieve controllable inductance gradient, the inner electrode line (3) is formed on the upper surface of the NiZnCuFeO3 slurry layer (2) by printing, and the FeSiCr prepreg (1), the NiZnCuFeO3 slurry layer (2) and the inner electrode line (3) are stacked in sequence for several times.

Citation Information

Patent Citations

  • Broadband high-permeability ferrite raw material belt and method for manufacturing same into chip-inductor element

    CN103113094A

  • Inner electrode silver paste for laminated inductor and preparation method thereof

    CN103915132A

  • Manufacturing method of chip inductor and chip inductor

    CN111354562A

  • Manufacturing method of laminated chip type power inductor

    CN111584222A

  • Laminated power inductor and preparation method thereof

    CN115732188A